Boruta-grid-search least square support vector machine for NO2 pollution prediction using big data analytics and IoT emission sensors - Habeeb Balogun; Hafiz Alaka; Christian Nnaemeka Egwim (Applied Computing and Informatics)
Purpose – This paper seeks to assess the performance levels of BA-GS-LSSVM compared to popular standalone algorithms used to build NO2 prediction models. The purpose of this paper is to pre-process a relatively large data of NO2 from Internet of Thing (IoT) sensors with time-corresponding weather and traffic data and to use the data to develop NO2 prediction models using BA-GS-LSSVM and popular standalone algorithms to allow for a fair comparison. Design/methodology/approach – This research installed and used data from 14 IoT emission sensors to develop machine learning predictive models for NO2 pollution concentration. The authors used big data analytics infrastructure to retrieve the large volume of data collected in tens of seconds for over 5 months. Weather data from the UK meteorology department and traffic data from the department for transport were collected and merged for the corresponding time and location where the pollution sensors exist. Findings – The results show that the hybrid BA-GS-LSSVM outperforms all other standalone machine learning predictive Model for NO2 pollution. Practical implications – This paper's hybrid model provides a basis for giving an informed decision on the NO2 pollutant avoidance system. Originality/value – This research installed and used data from 14 IoT emission sensors to develop machine learning predictive models for NO2 pollution concentration.